1962
DOI: 10.1021/jm01241a017
|View full text |Cite
|
Sign up to set email alerts
|

2-Substituted Cyclopropylamines. I. Derivatives and Analogs of 2-Phenylcyclopropylamine

Abstract: Fungistatic and bacteriostatic assays were performed by a serial dilution method which has been described previously.1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Optical activity was determined by sending samples for analysis to Robertson Microlite laboratories. While the purity of the isomers was not specifically tested, the optical activity of the separated isomers were nearly identical to that of Kaiser et al, which was reported for the (−) and (+) isomers to be: −30.5 and +31.0 (Kaiser et al, 1962). …”
Section: Methodssupporting
confidence: 71%
See 1 more Smart Citation
“…Optical activity was determined by sending samples for analysis to Robertson Microlite laboratories. While the purity of the isomers was not specifically tested, the optical activity of the separated isomers were nearly identical to that of Kaiser et al, which was reported for the (−) and (+) isomers to be: −30.5 and +31.0 (Kaiser et al, 1962). …”
Section: Methodssupporting
confidence: 71%
“…The positive and negative stereoisomers were purified from (±)TCP as a tartrate salt following established methods previously described (Kaiser et al, 1962). In short, we combined equal amounts of D-tartaric acid (0.1 moles) with the racemic form of TCP in ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…2‐PCPA ( 1 ) was first synthesized by Burger and Yost in 1948 and later, a series of 2‐PCPA derivatives and their MAO‐inhibitory properties were reported . Among all these compounds, 1 was developed as a clinical antidepressant, which is nonselective toward multiple forms of MAO .…”
Section: Introductionmentioning
confidence: 99%
“…Tranylcypromine (d, l-trans-2-phenylcyclopropylamine) was synthetized by Burger and Yost in 1948 (11). The stereoisomers of tranylcypromine were synthetized by Kaiser and coworkers at Smith Kline & French Laboratories in Philadelphia in 1962 (21). The absolute configuration of tranylcypromine stereoisomers was reported by Riley and Brier in 1972 (33).…”
Section: Introductionmentioning
confidence: 99%